SHOGUN: An Integrated Dashboard for Vulnerability Analysis via Internet-Wide Search Engines - Matos, Isabelle; Ponce, Lucas M; Cunha, Igor; Almeida, Pedro; Fazzion, Elverton; Cunha, Ítalo; Hoepers, Cristine; Steding-Jessen, Klaus; Chaves, Marcelo H. P. C.; Guedes, Dorgival; Meira Jr, Wagner (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2026: Anais Estendidos do XXVI Simpósio Brasileiro de Cibersegurança, 2026)
The increasing exposure of digital assets on the Internet demands efficient solutions for identifying and continuously monitoring vulnerabilities. While search engines like Shodan provide a targeted retrieval of exposure data, longitudinal risk assessment requires extensive data preparation. To bridge this gap, we present SHOGUN, an interactive dashboard engineered for the multidimensional analysis of internet-wide vulnerability data. Built upon a decoupled architecture, our tool abstracts raw search engine dumps into structured analytical datasets. The tool features a reactive web interface that combines geospatial and statistical visualizations with a cross-view drill-down navigation model, allowing security analysts to transition from macro-level network overviews to granular, asset-level forensic investigations.